Scheduling Algorithms for Under Water Sensor Networks: Recent Approaches and Open Challenges - Vasavada, Tejas Mukesh (INFOCOMP Journal of Computer Science, 2021)
The research domain of UWSN (Under Water Sensor Networks) is gaining wide attention these days. The sensors are deployed on the sea surface or seabed for monitoring, data collection or surveillance purpose. Unlike terrestrial networks, the UWSNs use acoustic signals for data communica- tion. The speed and bandwidth of acoustic signals is low compared to radio signals which are used in conventional terrestrial WSNs (Wireless Sensor Networks). As a result, protocol design in UWSN must be addressed separately than terrestrial networks. In this work, we have reviewed TDMA (Time Divi- sion Multiple Access) protocols for channel access. As TDMA is a collision-free method, it is preferred over other methods like random access methods or handshaking based medium access protocols. Some open issues are also proposed as follows: (i) It is found that very less or no work is done in the area of joint scheduling and topology formation for UWSNs. (ii) The problem of balancing schedule length of sink-rooted trees in multiple sinks UWSNs is also unattempted.